2019
DOI: 10.3928/24748307-20181113-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Income Mediate Racial/Ethnic Asthma Disparities

Abstract: Background: Health literacy and socioeconomic status (SES) are associated with both race/ethnicity and asthma outcomes. The extent to which health literacy and SES mediate racial/ethnic asthma disparities is less clear. Objective: To determine if health literacy and SES mediate racial/ethnic asthma disparities using advanced mediation analyses. Methods: A secondary analysis was performed using a Chicago-based longitudinal cohort study conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…This study found that educational attainment is associated with limited health literacy, echoing findings elsewhere in the literature [ 16 , 23 ]. Although limited health literacy is associated with a range of socio-demographic characteristics, it tends to affect vulnerable populations disproportionately, including people with lower educational attainment, of lower socioeconomic status, people from ethnic minorities, and those whose spoken language differs from the majority population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study found that educational attainment is associated with limited health literacy, echoing findings elsewhere in the literature [ 16 , 23 ]. Although limited health literacy is associated with a range of socio-demographic characteristics, it tends to affect vulnerable populations disproportionately, including people with lower educational attainment, of lower socioeconomic status, people from ethnic minorities, and those whose spoken language differs from the majority population.…”
Section: Discussionsupporting
confidence: 87%
“…A review of health literacy definitions by Sørensen et al (2012) describes health literacy as an individual’s knowledge, motivation and competence to assess, understand, appraise and apply health information to make healthcare decisions, and exercise disease prevention and health promotion throughout the life course [ 22 ]. Factors that mediate limited health literacy among people with asthma include socio-demographic factors, such as income, educational attainment, social support, and employment [ 16 , 23 ]. Other factors include ethnicity, cultural background and language [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In a recent analysis of adults living in Chicago with persistent asthma, low health literacy and low income mediated the association between race and ethnicity and lower quality of life and ED visits owing to asthma. 37 Connected to both low income and lower educational achievement, racial and ethnic minority populations have reduced employment opportunity, which is reflected clearly in the current US unemployment rates that continue to be higher for Black and Latinx Americans than White Americans. 38 Lack of employment benefits, such as paid leave, sick time, and employer health insurance, contributes to health inequities.…”
Section: Education and Employmentmentioning
confidence: 99%
“…The burden of low health literacy disproportionately affects the most socially and economically marginalized groups [ 18 - 21 ]. Through an intersectional lens, we can see the cumulative effects in health care through the experiences of those with low health literacy and other vulnerabilities.…”
Section: The Covid-19 Infodemicmentioning
confidence: 99%